A Simple Measure of Food Consumption Diversification for Identifying Family Food Insecurity - . Hardinsyah; Sri Rihati Kusno; Ali Khomsan (Media Gizi dan Keluarga, 2000)
The objective of this study was to develop a simple and appropriate method of measuring food consumption diversification (FD) in relation to food security and nutritional quality of the diet (NQ). In this method family food consumption is grouped into five major food groups, FMF (staple food, meats/side dish, vegetables, fruit, and milk), which are counted by applying using adult male consumer¡¦s unit. The NQ is defined as the mean nutrient adequacy of eighth nutrients (i.e. energy, protein, ferrum, calcium, phosphorus, vitamin A, vitamin B1, and vitamin C.)Eighth measures of FD were developed. The first two measurements were developed based on the quantity of five major food group (FMF) consumed, namely score 53 and score 54. While the other six alternative measurements were based on score 53 is the FD measurement based on FMF and 3 level of number of kinds of food consumed, that are (1) number of kinds of staple food, (2) number of kinds of side dish, (3) number of kinds of vegetables, (4) number of kinds of fruit, (5) number of kinds of milk, (6) total of number of kinds of food consumed.Among the 8 measurements based on number of kinds of food consumption diversification measurement based on total of food kinds of five food groups is the most valid although the validity is lower than food consumption measurement based on number of food consumption (score 53 and score 54). The result shows that the simplest and most valid measurement of FD is score 53, the score that based on the amount of consumption of five food groups (staple food, side dish, vegetables, fruits, and milk) by implementing score system of 3 level category. The score 53 shows not only the NQ as a whole but shows that nutrient adequacy of each nutrient as well.